(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2025)
This paper examines the pivotal term δύναμις in Aristotle’s definition of tragedy Poetics (6, 1450b17-20), where he states: «The δύναμις of tragedy exists even without contest and actors». Through close analysis of Poetics 6, the study contrasts two interpretations: δύναμις as ‘effectiveness’ (prioritizing the text’s autonomous cathartic power) versus ‘potentiality’ (emphasizing tragedy’s inherent orientation toward theatrical performance). By tracing Aristotle’s shifting definitional models—from genus-differentia to hylomorphic—the paper resolves this tension by distinguishing tragedy’s creative process (where plot is potential for performance) from its receptive experience (where textual effectiveness alone suffices for catharsis). Key passages (Poet. 14, 26; Met. IX) confirm that while tragic δύναμις operates textually as a self-sufficient ‘principle of change’, its compositional logic remains scenically constrained. The study concludes that δύναμις denotes effectiveness in fruition but presupposes potentiality in creation, reconciling text and performance centered readings.